Redescription of Mastigias papua (Scyphozoa, Rhizostomeae) with designation of a neotype and recognition of two additional species - Souza, Mariana Rocha De; Dawson, Michael N (Zootaxa, 2018)
Mastigias, the ‘golden’ or ‘spotted’ jellyfish, is distributed throughout the Indo-Pacific. Specimens are identified routinely as Mastigias papua, although eight species were described historically, and molecular analyses evince at least three phylogenetic species. Understanding species diversity in Mastigias has become a priority because of its growing relevance in studies of boom-bust dynamics related to environmental change, cryptic species, local adaptation, parallel evolution, and peripatric speciation. However, species delimitation and identification are inhibited by a dearth of type specimens for most species, including M. papua. We address these issues by resampling Mastigias from the type locality in Waigeo, West Papua, as well as in the Philippines, and by comparing cytochrome c oxidase subunit I and up to 34 morphological characters of 268 Mastigias specimens from surrounding regions in the Indo-Pacific. We also gathered data from the historical descriptions of the eight species of Mastigias to estimate the identity of the two other currently revealed clades. Using this integrative taxonomic approach, we re-describe Mastigias papua as endemic to the tropical western Pacific islands (including Papua, Palau, Enewetak) and designate a neotype for the species. Additionally, based on morphological similarity and geographic overlap, we identified a second clade most probably as M. albipunctatus (from Japan, Komodo, Berau and Philippines) and a third clade tentatively as either M. andersoni or M. ocellatus. This study highlights the benefits of combining molecular analyses, samples from type locations, traditional descriptions and statistical analyses of morphological variation in systematic studies, and the concomitant potential of such studies to increase understanding of evolutionary patterns and processes in Scyphozoa.